2004
DOI: 10.1017/s0074180900197876
|View full text |Cite
|
Sign up to set email alerts
|

Gas Outflows in Radio Galaxies

Abstract: Abstract.We present a summary of our recent results on gas outflows in radio galaxies. Fast outflows (up to 2000 km S-l) have been detected both in ionized and neutral gas. The latter is particularly surprising as it shows that, despite the extremely energetic phenomena occurring near an AGN, some of the outflowing gas remains, or becomes again, neutral. These results are giving new and important insights on the physical conditions of the gaseous medium around an AGN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 18 publications
(18 reference statements)
1
7
0
Order By: Relevance
“…Recent observations done with the new broad-band system at the WSRT have given further insight the characteristics of the absorption. These observations show that the broad absorption is much wider than measured before by Mirabel (1989), covering now a range in velocities of about 2000 km s −1 ; most of this H I absorption is blueshifted (see Morganti et al 2003a and the profile shown in Fig. 2).…”
Section: Introductionsupporting
confidence: 53%
“…Recent observations done with the new broad-band system at the WSRT have given further insight the characteristics of the absorption. These observations show that the broad absorption is much wider than measured before by Mirabel (1989), covering now a range in velocities of about 2000 km s −1 ; most of this H I absorption is blueshifted (see Morganti et al 2003a and the profile shown in Fig. 2).…”
Section: Introductionsupporting
confidence: 53%
“…The bulk H i kinetic luminosities represent about a few percent of the Eddington luminosities. This is two orders of magnitude larger than the ionized outflow kinetic power (Holt et al 2006;Morganti et al 2007Morganti et al , 2010. We will further discuss these results in Section 6.2 when examining the transfer of kinetic energy from the jet to the H i and H 2 gas.…”
Section: H I Gasmentioning
confidence: 93%
“…Tadhunter 1991;Tadhunter et al 2001;Holt et al 2003;van Bemmel et al 2003;and Morganti et al 2004, for a summary of recent results). However, it is intriguing that in several radio sources fast outflows of neutral hydrogen (up to 2000 km s −1 ) have been discovered.…”
Section: Introductionmentioning
confidence: 99%